2005
DOI: 10.1177/0047287504272033
|View full text |Cite
|
Sign up to set email alerts
|

International versus Domestic Visitors: An Examination of Destination Image Perceptions

Abstract: Potential tourists use various destination attributes to aid in destination image formation. Destination environmental attributes related to the actual product or site have been shown to influence destination image. These environmental attributes can be grouped into two subcategories—destination atmospherics and destination service. This study identified significant differences in the ratings of these two categories when comparing three groups of visitors to Florida: Florida (in-state) residents, U.S. domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(143 citation statements)
references
References 20 publications
9
129
1
4
Order By: Relevance
“…This supports researchers who have adopted a combined segmentation approach involving two (e.g. Bansal & Eiselt, 2004;Bonn et al, 2005;Kim et al, 2003;Sarigollu & Huang, 2005) to four (e.g. Becken et al, 2003;Beh & Bruyere, 2007;Chang, 2006;Frochot, 2005) segmentation bases.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This supports researchers who have adopted a combined segmentation approach involving two (e.g. Bansal & Eiselt, 2004;Bonn et al, 2005;Kim et al, 2003;Sarigollu & Huang, 2005) to four (e.g. Becken et al, 2003;Beh & Bruyere, 2007;Chang, 2006;Frochot, 2005) segmentation bases.…”
Section: Discussionsupporting
confidence: 80%
“…To date, studies have profiled tourists for a single destination (e.g. Andreu et al, 2005;Bloom, 2005;Bonn et al, 2005;Johns & Gyimothy, 2002) with less emphasis on comparing tourists for different stakeholder groups (e.g. Laws et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that tourists usually choose a destination with the most favorable image (Gartner, 1989;Leisen, 2001; 38 JHTI 1,1 Dadgostar and Isotalo, 1996). In addition, destination image has a direct impact on travel behavior and plays a critical role in the destination choice process (Bonn et al, 2005).…”
Section: Literature Review Destination Imagementioning
confidence: 99%
“…Although less researched, significant behavioral differences have also been recorded between domestic and international tourists. Evidence indicates that domestic tourists have different travel motivations compared to international tourists [7,8], as well as varying destination image perceptions [9], information search behavior and source preferences when trip-planning [10], recreational and shopping choices [11][12][13][14][15], service expectations [16,17], and degrees of destination loyalty and satisfaction [18]. The greater distances traveled by international tourists, including often-increased holiday length, are thought to be key factors that influence this behavioral difference from domestic visitors [13,15,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%